Determination of Health Literacy among End Stage Renal Disease Patients - Zahraa A.Jassem, Ibrahim A. Al-Ashour (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Patients with end-stage renal disease require hemodialysis treatment to maintain renal function and need adequate health literacy skills to manage symptoms that may arise and cope with physical, psychological and financial changes. In addition, the patients are expected to be able to make their own decisions on how to manage the disease and adhere to treatment. The Study aimed to assess health literacy levels among end-stage renal disease patients. Methodology: A descriptive A-non-probability (purposive sample) of (171) male and female hemodialysis patients in al-Najaf al-Ashraf city of patients with end-stage renal disease and undergoing hemodialysis. Most patients were diagnosed with ESRD > one year ago from those who have been on a maintenance hemodialysis program for more than a year. Data were analyzed by using descriptive data analysis (frequencies, percentages, mean, standard deviation, Fisher’s exact test). Results: Our results show that the overall assessment of patient health literacy level is Inadequate at the mean score of (20.98), also assessment according to the three-domain (health care, disease prevention and health promotion) result shows the lowest mean index at health promotion (18.560 ) with a high percentage in the difficulty of responses (66.7%) Conclusions: The study concluded that End-stage renal disease Patients undergoing hemodialysis have an inadequate level of health literacy. They reflect difficulties in understanding and processing health information, which may interfere with therapeutic management and self-care decisions making about their health Keywords: Determination, Health Literacy, Renal Disease.